2020
DOI: 10.1039/c9sc05969e
|View full text |Cite
|
Sign up to set email alerts
|

Base induced isomerisation of a phosphaethynolato-borane: mechanistic insights into boryl migration and decarbonylation to afford a triplet phosphinidene

Abstract: We report on the (tert-butyl)isocyanide-catalysed isomersation of a phosphaethynolato-borane, [B]OCPto its linkage isomer, a phosphaketenyl-borane, [B]PCO. Mechanistic insight into this unusual isomerisation was gained through a series of stoichiometric reactions of [B]OCP with isocyanides and theoretical calculations at the Density Functional Theory (DFT) level. [B]PCO decarbonylates under photolytic conditions to afford a novel boryl-substituted diphosphene, [B]P]P[B]. This reaction proceeds via a transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 53 publications
4
44
0
4
Order By: Relevance
“…All reactions and product manipulations were carried out under an inert atmosphere of argon or dinitrogen using standard Schlenk‐line or glovebox techniques (MBraun UNIlab glovebox maintained at <0.1 ppm H 2 O and <0.1 ppm O 2 ). [B]OCP, [B]PCO and tris(pentafluorophenyl)borane were synthesized according to previously reported synthetic procedures . Hexane (hex; Sigma Aldrich, HPLC grade), and toluene (Sigma Aldrich, HPLC grade) were purified using an MBraun SPS‐800 solvent system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reactions and product manipulations were carried out under an inert atmosphere of argon or dinitrogen using standard Schlenk‐line or glovebox techniques (MBraun UNIlab glovebox maintained at <0.1 ppm H 2 O and <0.1 ppm O 2 ). [B]OCP, [B]PCO and tris(pentafluorophenyl)borane were synthesized according to previously reported synthetic procedures . Hexane (hex; Sigma Aldrich, HPLC grade), and toluene (Sigma Aldrich, HPLC grade) were purified using an MBraun SPS‐800 solvent system.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of tris(pentafluorophenyl)borane, related reactions are only possible using more reactive substrates, such as allenyl ketones and isocyanates . It is these latter studies, as well as related work exploring the hydroboration of phosphaalkynes, that prompted us to explore the reactivity of BCF towards two isomeric forms of a boryl‐phosphaethynolate, [B]OCP and [B]PCO (where [B]= N , N’ ‐bis(2,6‐diisopropylphenyl)‐2,3‐dihydro‐1 H ‐1,3,2‐diazaboryl) . Interestingly, these reactions give rise to three different borylated phosphaalkenes with the same molecular formula.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Moreover,B ertrand observed that irradiation of (L)PÀPCO in the presence of AdNC affords disubstituted (L)P À PCN À Ad (Ad = 1-adamantyl), [9] whereas Goicoechea described how t BuNC catalyzes linkage isomerization between (L)B À OCP and (L)B À PCO,e ventually affording (L)BÀPCNÀ t Bu upon decarbonylation. [10] Given the persisting EÀPl inkages,t he above isocyanide conversions are best construed as phosphinidene transfer reactions.H owever, Na(OCP) itself could engage in Pa tom transfer reactivity, which has gained momentum in main group [11] and transition metal [12] chemistry.A ne nticing possibility along these lines would be to generate amonosubstituted cyanophosphide:By virtue of steric accessibility,s uch an RÀNCP À unit could engage in more unrestrained bonding interactions than disubstituted analogues prepared via phosphinidene transfer. Moreover,r educed forms of monosubstituted cyanophosphide remain unknown, posing the question whether these fragments are too reactive to engage in redox activity.Given the isoelectronic relationship between P À and S, we pursued the conversion of an isocyanidet ot he phosphorus analogue of an organic isothiocyanate,R ÀNCP À , via Pa tom transfer from Na(OCP), and extended this methodology to As to form the heavier cyanoarsenide congener,R À NCAs À ,u sing ad ivalent Ti center as the reductant.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Due to its ambident nucleophilic character, it binds to soft centers [27][28][29][30][31][32] via the phosphorus atom (M-PvCvO) and hard centers via the oxygen atom (M-O-CuP). [33][34][35][36][37][38][39] Furthermore, phosphaketenes ([M]-PvCvO) with [M] = main group element or transition metal fragment show a tendency to lose carbon monoxide which allows to prepare mono-and polynuclear metal phosphides. 23,33,[40][41][42][43][44][45][46][47] There are very few examples which show a bridging OCP-unit between two metal centers.…”
Section: Introductionmentioning
confidence: 99%